2018
DOI: 10.1590/s1984-296120180061
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii: infection among shelter and stray cats in Rio de Janeiro, Brazil

Abstract: The aim of this study was to identify possible infection of Toxoplasma gondii among cats in a shelter and a set of condominiums in the city of Rio de Janeiro, through changes to the cats' serological status between two different times in 2014 and 2015. One group was made up of captive cats at the municipal shelter and the other comprised stray cats that circulated in condominiums in the city. On the first occasion, cats were caught and tagged through application of microchips; in this manner, blood samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
1
8
1
4
Order By: Relevance
“…However, these results should be interpreted with caution due to the short duration of the present study. Other studies detected changes in serological status in 9.1% (Afonso et al, 2006) and 18% (Pereira et al, 2018) of cats, but they had longer sampling intervals (11 years and 4-8 months, respectively). On the other hand, MAT titres were maintained over time in all seropositive individuals, except in one cat with a low titre (1:25) that had a negative result after approximately 1 month.…”
Section: Discussionmentioning
confidence: 88%
“…However, these results should be interpreted with caution due to the short duration of the present study. Other studies detected changes in serological status in 9.1% (Afonso et al, 2006) and 18% (Pereira et al, 2018) of cats, but they had longer sampling intervals (11 years and 4-8 months, respectively). On the other hand, MAT titres were maintained over time in all seropositive individuals, except in one cat with a low titre (1:25) that had a negative result after approximately 1 month.…”
Section: Discussionmentioning
confidence: 88%
“…This restriction of the circulation environment may minimize the exposure of felines to the outdoor environment, possibly contaminated with T. gondii oocysts and inhabited by potential chronically infected intermediate hosts. It is important to highlight that the stray cat populations, resident in different areas of Rio de Janeiro city, are exposed to T. gondii, suggesting that these animals may be contributing to the contamination of the environment by oocysts in the study area [7,51,61].…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of IgG anti-T. gondii antibodies, commercial anti-Cat IgG produced in goats, BioRad Ò and anti-Dog IgG produced in rabbit Sigma-Aldrich Ò conjugates diluted in Evans Blue solution were used. The samples were considered positive when total fluorescence of the tachyzoite surface was observed, with titers equal to or greater than 1:16 in dogs and 1:64 in cats [5,61].…”
Section: Blood Collection and Serological Testmentioning
confidence: 99%
“…Epidemiological studies in Latin American countries have shown a high frequency of T. gondii infection in stray dogs and cats strongly associated with the region, the animal species and the type of diagnostic test used. Studies conducted in Brazil displayed variations in urban regions of the cities of São Paulo (dogs—50.5%, cats—40.0%), Rio de Janeiro (cats—18%) and Curitiba (dogs—48%), where a high percentage of positivity was observed in both dogs and cats [ 16 , 17 , 18 ]. In Argentina and Chile, the majority of the reports are studies carried out on pets.…”
Section: Introductionmentioning
confidence: 99%